Evaluation and Management of Bloody Nipple Discharge - عمران علي; علّوش علي; مسعود سجيع (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: Nipple discharge is an important complaint among women who visit breast clinics around the world. 50% to 80% of women of childbearing age suffer from nipple discharge, and it is the third most common after breast pain and palpation. Lumps in the breast, and the color of discharge is always the first warning symptoms for the patient and the treating physician.Blood discharge is the most important symptom among the types of discharge, although it is caused by benign lesions in most cases, malignancy is the cause of it in varying proportions in patients (5% to 33%), according to the findings accompanying the examinations and investigations, which causes a high degree of concern and fear among women. The importance of this study comes from the high level of anxiety and fear in patients caused by the appearance of bloody discharge from the nipple, and because of the difficulty of distinguishing between benign and malignant lesions might cause this complaint without surgical excision and histological examination, it is necessary to examine and investigate patients early. Research methods: The study included all patients who attended Tishreen University Hospital in Lattakia with a complaint of nipple discharge with an undiagnosed cause during a period of two years (2019-2021) and who eventually underwent a surgical procedure, as patients with previously known and confirmed causes by histological examination were excluded, as well as Patients who did not eventually undergo surgery as a diagnostic and therapeutic measure for this problem. Results: During a period of two years between 2019-2021, 60 patients underwent examinations and investigations before surgery and then surgically operated for undiagnosed nipple hemorrhage in the General Surgery Department of Tishreen University Hospital. The characteristics of the discharge in the study sample were as follows: 80% of the leakage is spontaneous, 88.3% is unilateral, 73% is continuous, and 88.3% is from one duct. As for the duration of bleeding, in 33.3% it was of the sample for less than a week and 41.7% for less than two weeks. After the cytological examination of the discharge fluid, it was found that 11.7% of the sample were malignant cells, the largest percentage was 55% normal cells, and 33.3% were suspicious cells. the initial diagnosis was appeared to us that 33.3% of the sample had a papilloma, 11.7% ductal dilatation, 10% fibrocystic changes, 33.3% suspected breast cancer and 11.7% breast cancer. Upon final diagnosis, 26.6% of the sample had papilloma, 50.0% breast cancer, 13.4% fibrocystic changes, and 10% ductal dilatation. Conclusions: In our study Cancer is responsible for nipple discharge in (50%) of cases, followed by papilloma in 26.6% and fibrocystic changes 13.4%. The characteristics of the leakage in patients with papillary tumors, fibrocystic changes and ductal ectasia were not compatible with the characteristics of the normal secretion, but were similar to the characteristics of the leakage in patients with breast cancer. The presence of a palpable mass by clinical examination and/or seen by ultrasound is one of the most common findings frequently associated with breast cancer (50.0% of breast cancer patients).